Desempenho muscular durante a protração e retração da escápula em sujeitos com instabilidade glenoumeral traumática anterior - Netto, Walter Ansanello (2014)
Traumatic anterior glenohumeral instability makes the humeral head unable to remain centered on the glenoid fossa and alters the arthrokinematics and the strength of the shoulder rotators. The rotator cuff muscles depend on a good performance of the scapular muscles and their strengthening has been recommended at different levels for subjects with traumatic anterior glenohumeral instability. On the other hand, poor scapular performance is not well described in this population. Therefore, the aim of this thesis was to investigate muscle performance during protraction and retraction of the scapula in the sagittal and scapular planes in subjects with traumatic anterior glenohumeral instability. The study included 40 volunteers of both sexes, divided into two groups: control group (n = 20) and patients with traumatic anterior glenohumeral instability (n = 20). Muscle performance during protraction and retraction was assessed using Biodex System III isokinetic dynamometer in the isometric mode, with three repetitions, and in the concentric isokinetic mode, at the speeds of 12.2 cm/s and 36.6 cm/s, with 5 and 10 repetitions, respectively. The evaluations were performed with the shoulder flexed at 90° in the sagittal plane and elevated at 90° in the scapular plane. The mean peak force, total work and the total range of motion (ROM) were the variables of interest. The variables were compared using analysis of variance with two factors (ANOVA - Two Way), considering plans as the withinsubject factor and group as the between-subject factor, at a significance level of 5%. There was difference between subjects in the average peak force at isometric protraction and retraction and also at protraction during isokinetic evaluation at 36 cm/s (p <0.05). For intra-subject analysis (scapular plane vs sagittal plane), differences were found for mean peak force during isometric protraction, isokinetic protraction at 12.2 cm/s and isokinetic protraction at 36.6 cm/s. There was an interaction for the total work in retraction at 12.2 cm / s, total work in retraction at 36.6 cm / s for ROM. This dissertation shows that subjects with traumatic anterior glenohumeral instability have decreased strength in protraction and in isometric retraction and also in isokinetic contraction. Average peak force, total work and ROM in the sagittal plane are higher than in the scapular plane.